2022
DOI: 10.1002/admi.202102395
|View full text |Cite
|
Sign up to set email alerts
|

How to Make a Surface Act as a Micropump

Abstract: In this paper, the phenomenon of light‐driven diffusioosmotic (DO) long‐range attractive and repulsive interactions between micro‐sized objects trapped near a solid wall is investigated. The range of the DO flow extends several times the size of microparticles and can be adjusted to point towards or away from the particle by varying irradiation parameters such as intensity or wavelength of light. The “fuel” of the light‐driven DO flow is a photosensitive surfactant which can be photo‐isomerized between trans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…Similar to the rigid porous particles, we explain this observation by the dissimilar photoisomerization rate of the surfactant inside the microgel and in the bulk, ,, which creates an excess of cis -isomer concentration Δ c C near the microgels in comparison to the bulk soltion. We have demonstrated that the DO flow velocity scales linearly with Δ c C ( t ), where the dependence of Δ c C on time is estimated by solving the equation where k TC , MG and k TC are the rate constants of trans – cis isomerization inside the microgel and bulk solution, respectively, k CT is the rate constant of cis – trans isomerization in the bulk solution, c T,MG is the trans -isomer concentration in the microgel, c T,B and c C,B are the concentrations of trans- and cis- isomers in the bulk, and I is the intensity of the light (an illustration of the process is provided in Figure S3, Supporting Information). In the following, we demonstrate how three experimental parameters, i.e., (1) wavelength of irradiation, (2) amount of charged groups within the gel, and (3) intensity of light, determine the extent of the DO flow generated around and by the microgels.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Similar to the rigid porous particles, we explain this observation by the dissimilar photoisomerization rate of the surfactant inside the microgel and in the bulk, ,, which creates an excess of cis -isomer concentration Δ c C near the microgels in comparison to the bulk soltion. We have demonstrated that the DO flow velocity scales linearly with Δ c C ( t ), where the dependence of Δ c C on time is estimated by solving the equation where k TC , MG and k TC are the rate constants of trans – cis isomerization inside the microgel and bulk solution, respectively, k CT is the rate constant of cis – trans isomerization in the bulk solution, c T,MG is the trans -isomer concentration in the microgel, c T,B and c C,B are the concentrations of trans- and cis- isomers in the bulk, and I is the intensity of the light (an illustration of the process is provided in Figure S3, Supporting Information). In the following, we demonstrate how three experimental parameters, i.e., (1) wavelength of irradiation, (2) amount of charged groups within the gel, and (3) intensity of light, determine the extent of the DO flow generated around and by the microgels.…”
Section: Resultsmentioning
confidence: 87%
“…The gradient in the osmotic pressure is formed near the particle, thus a local -light driven diffusioosmotic ( l -LDDO) flow . Examples of such particles are silica colloids having pores of nanometer size and rough surfaces such as wood, dust, soil, sand, hair, and so on . For spherical particles, the flow is directed radially and results in long-range diffusioosmotic repulsion or attraction (wavelength dependent) in an ensemble of the colloids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feldmann et al [73] could pump tracer particles due to a photosensitive surfactant, which changed from trans to cis state with UV light. The same surfactant was later used by Bekir et al [60] to create a micropump.…”
Section: Applications Of Diffusio-osmosismentioning
confidence: 99%
“…Michelin and Lauga [59] developed a universal optimal geometry to create a pumping wall in a microchannel based on chemically active patches with non-zero phoretic mobility. Bekir et al [60] created a micropump by light-driven diffusio-osmosis, where the surfactant changes from trans to cis states depending on the light wavelength. The surfactant is adsorbed by a particle in the trans state, while the cis state prefers the solution, which creates a strong concentration difference based on adsorption and desorption.…”
Section: Applications Of Diffusio-osmosismentioning
confidence: 99%